Laccases in Bioremediation and Waste Valorisation - Schlosser, Dietmar; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This Microbiology Monographs volume covers the latest advances in laccase applications in bioremediation and waste valorisation. The first three chapters provide a comprehensive introduction to fungal and bacterial laccases (the two most important enzyme groups from an application viewpoint) and their practical use in bioremediation and lignocellulosic waste valorisation. Subsequent chapters discuss possible combinations of laccases and further potentially collaborating enzymes, and offer in-depth insights into laccase immobilisation for wastewater treatment and environmental biosensor applications of laccases. Lastly, the book addresses the quest for enzymes with improved and better-fitting properties, covering laccase engineering by directed and computational evolution, and novel enzymes from extreme environments. As such, it is a fascinating read for microbiologists in both industry and academia. .
Fungal Laccases and Their Potential in Bioremediation Applications -- Bacterial Laccases: Some Recent Advances and Applications -- Old Enzymes at the Forefront of Lignocellulosic Waste Valorisation -- Laccases in the Context of Potentially Cooperating Enzymes -- Immobilized Laccase: A Promising Bioremediation Tool for the Removal of Organic Contaminants in Wastewater -- Challenges in Applying Cross-Linked Laccase Aggregates in Bioremediation of Emerging Contaminants from Municipal Wastewater -- Laccase-Assisted Cues: State-of-the-Art Analytical Modalities for Detection, Quantification, and Redefining (3z(BRemoval(3y (Bof Environmentally-Related Contaminants of High Concern -- Laccase Engineering by Directed and Computational Evolution -- Laccases from Extremophiles.s
Keywords: Enzymology; Microbiology; Bacteriology; Microbial ecology; Enzymology; Applied Microbiology; Bacteriology; Eukaryotic Microbiology; Microbial Ecology